PENYULUHAN DAN PERCONTOHAN DESAIN PENGEMBANGAN RUMAH SUBSIDI YANG SEHAT DAN NYAMAN BAGI PENGHUNI - Giska Ayu Pradana Putri Kamase; Teti Handayani; Zaedar Gazalba (Universitas Mataram, 2022)
Subsidized housing falls into Rumah Sangat Sederhana (RSS) category which is built on relatively small land with a limited floor area. Hence, the owners often undertake development to fulfilling their needs. Most of the time, however, the results are still far from health and comfort standards. Griya Pesona Alam Housing which is located in Dasan Geria, Lingsar District, West Lombok Regency, is selected as the location for this public service activity. This activity aims to provide design recommendations for subsidized housing development while considering architectural design aspects, occupants’ health and comfort. In general, the activities are divided into 3 (three) main phases, namely the problem identification phase, the problem settlement analysis phase, and the implementation phase. All these phases include initial survey dan observation, literature dan policy study, building design, and community counselling. Occupants have to consider natural lighting, ventilation, temperature, and humidity level to achieve indoor health and comfort. An addition, adequate circulation also needs to be considered to achieve spatial comfort. All these aspects are guidelines for developing health and comfort building. They are being addressed in an applicative design recommendation. The counselling process includes exemplary and design consultation with the community. The activity has produced a design recommendation which paid attention to adequate circulation, ventilation and natural lighting, which is expected to improve occupants’ knowledge and awareness.